(untitled) (World Bulletin of Public Health, 2024)
In this study, the authors presented an assessment of the comparative effectiveness of laparoscopic surgery and open surgery in the treatment of colorectal cancer. 92 patients with histologically verified colorectal cancer were included in this study. By randomization, patients were divided into a control group (open surgery, n = 46 cases) and a study group (laparoscopic surgery, n = 46 cases). The duration of the operation (122.54 ± 14.85) min and the length of the incision (4.51 ± 1.065) cm were shorter in the study group compared to the control group. Intraoperative blood loss in the main group was (161.12 ± 10.694) ml, versus the control group (218.53 ± 15.369) ml (p<0.05). Patients in the main group had a higher five-year survival rate and a lower incidence of postoperative complications compared to the control group (all P >< 0.05). Therefore, the use of laparoscopic surgery in the treatment of colorectal cancer has better clinical effect than open surgery and is worthy of clinical application.